Threats Related to Maternal Mortality in Kenya: A Systematic Review (British Journal of Multidisciplinary and Advanced Studies, 2023)
Given the high level of MMR in Kenya, this systematic review set out to systematically review studies on hazard quotients for maternal mortality in Kenya. The end goal of the review was to identify relevant empirical evidence that were included in the final study synthesis and answered the set research question and objectives. The addressed research question was ‘which are the elements of danger for maternal mortality in Kenya?’ Objectives of the study were to assess the socio-demographic risk factors for maternal mortality in Kenya and to determine the hospital based threats for maternal mortality in Kenya. Formulation of research question was guided by the population, exposure and outcomes (PEO) format. A qualitative systematic review design was adopted. The population under review was pregnant women and sample of the study included was 7. PubMed and Google Scholar were the databases used to access the included studies. CASP 2018 was used to appraise the selected/included studies. A qualitative synthesis was used by the study to present the results from the selected studies narratively. Study findings showed that individual level key risks for maternal mortality in Kenya included age, distance to healthcare centres, anaemia and labour complications. The results also showed that nurses’ attitude and mistreatment were among risk factors for ANC non-attendance and adverse health outcomes among pregnant women in Kenya. The study concludes that socio-demographic and hospital based risk factors affect MMR in Kenya and urgent steps have to be taken if SDG 3 is to be attained by the 2030 end date.